C5a complement and cytokine signaling mediate the pronociceptive effects of complex regional pain syndrome patient IgM in fracture mice. Issue 5 (May 2021) - Shi, Xiaoyou; Guo, Tian-zhi; Li, Wen-wu; Birklein, Frank; Escolano, Fabiola L.; Herrnberger, Myriam; Clark, J. David; Kingery, Wade S.
Abstract : Abstract: It has been proposed that complex regional pain syndrome (CRPS) is a posttraumatic autoimmune disease. Previously, we observed that B cells contribute to CRPS-like changes in a mouse tibia fracture model, and that early (<12 months duration) CRPS patient IgM antibodies have pronociceptive effects in the skin and spinal cord of muMT fracture mice lacking B cells. The current study evaluated the pronociceptive effects of intraplantar or intrathecal injections of early CRPS IgM (5 µg) in muMT fracture mice. Skin and lumbar spinal cord were collected for immunohistochemistry and polymerase chain reaction analyses. Wild-type mice exhibited postfracture increases in complement component C5a and its receptor expression in skin and spinal cord, predominantly on dermal macrophages and spinal microglia. Intraplantar IgM injection caused nociceptive sensitization in muMT fracture mice with increased complement component C1q and inflammatory cytokine expression, and these IgM effects were blocked by a C5a receptor antagonist (PMX53) or a global cytokine inhibitor (pentoxifylline). Intrathecal IgM injection also had pronociceptive effects with increased spinal cytokine expression, effects that were blocked by PMX53 or pentoxifylline treatment. Intrathecal injection of chronic (>12 months duration) CRPS patient IgM (but not IgG) caused nociceptive sensitization in muMT fracture mice, but intraplantar injection of chronic CRPS IgM or IgG had no effect. We postulate that CRPS IgM antibodies bind to neoantigens in the fracture limb skin and corresponding spinal cord to activate C5a complement signaling in macrophages and microglia, evoking proinflammatory cytokine expression contributing to nociceptive sensitization in the injured limb. Abstract : Supplemental Digital Content is Available in the Text.C5a complement and cytokine signaling mediates complex regional pain syndrome patient IgM pronociceptive effects in the skin and spinal cord of fracture mice.